Determinasi Niat Pembelian Produk Rumah Tangga Ramah Lingkungan di Indonesia: Pendekatan Theory of Planned Behavior - Dwita Prisdinawati; Mira Yanuarti; Febri Nur Pramudya (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the determinants of purchasing intentions for environmentally friendly household products in Indonesia using the Theory of Planned Behavior (TPB) approach. A quantitative approach with an explanatory survey design was applied to 350 respondents in three major cities Jakarta, Surabaya, and Yogyakarta who had purchased green products in the past year. The variables tested included environmental awareness, perceived quality, perceived price, and social influence. Regression analysis results showed that all variables had a significant effect on purchase intention, with an R² value of 0.63 and F = 34.21 (p < 0.01). Environmental awareness was the most dominant factor (β = 0.42), followed by quality perception (β = 0.31) and social influence (β = 0.28), while price had a negative effect (β = -0.25). These results confirm that the intention to purchase green products is driven more by psychological factors and social norms than by economic considerations. The implications of this study emphasize the importance of ecological education, product innovation, and fair pricing policies to strengthen the transition to sustainable consumption in Indonesia.